2019
DOI: 10.20886/jphh.2019.37.3.204-216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Cacat Pengeringan Dan Pemesinan Pada Empat Jenis Kayu Cepat Tumbuh Termodifikasi Panas

Abstract: Heat treatment is one method that can improve the quality of wood including for fast-growing wood species. However, this treatment can cause some drying defects as well as the change of machining properties after applying that heat treatment. The purpose of this study was to evaluate the effect of wood species and heating time on the drying and machining defects. The fast-growing wood species used were teak, mangium, jabon, and sengon. The heat treatment was carried out at a temperature of 165°C with variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The use of high temperatures to improve the quality of young teak wood has been carried out by several researchers (Garcia, Lopes, Nascimento, & Latorraca, 2014;Lopes, Garcia, & Nascimento, 2018;Adzkia, Priadi, & Karlinasari, 2019;Pasaribu & Sisilia, 2021;Martha et al, 2021). According to the research results of Adzkia et al (2019), the best machining quality can be obtained by using a temperature of 165ºC for 2 hours. However, Pasaribu and Sisilia (2021) reported that temperatures up to 170ºC for 2 hours and compacted by 25% will still experience a dimension change at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The use of high temperatures to improve the quality of young teak wood has been carried out by several researchers (Garcia, Lopes, Nascimento, & Latorraca, 2014;Lopes, Garcia, & Nascimento, 2018;Adzkia, Priadi, & Karlinasari, 2019;Pasaribu & Sisilia, 2021;Martha et al, 2021). According to the research results of Adzkia et al (2019), the best machining quality can be obtained by using a temperature of 165ºC for 2 hours. However, Pasaribu and Sisilia (2021) reported that temperatures up to 170ºC for 2 hours and compacted by 25% will still experience a dimension change at room temperature.…”
Section: Introductionmentioning
confidence: 99%